A pilot randomized controlled trial comparing nutritious meal kits and no-prep meals to improve food security and diet quality among food pantry clients - Kelseanna Hollis-Hansen; Carolyn Haskins; Jessica Turcios; Michael E. Bowen; Tammy Leonard; MinJae Lee; Jaclyn Albin; Benaye Wadkins-Chambers; Cynthia Thompson; Taylor Hall; Sandi L. Pruitt (BMC, 2023)
Abstract Background Food pantry clients have high rates of food insecurity and greater risk for and prevalence of diet-related diseases. Many clients face time, resource, and physical constraints that limit their ability to prepare healthy meals using foods typically provided by pantries. We compared two novel approaches to alleviate those barriers and encourage healthier eating: meal kits, which bundle ingredients with a recipe on how to prepare a healthy meal, and nutritious no-prep meals, which can be eaten after thawing or microwaving. Methods Participants were adult pantry clients from a large food pantry in the Southern sector of Dallas, Texas. We conducted a repeated measures between-subjects study with 70 clients randomized to receive 14-days of meal kits (n = 35) or no-prep meals (n = 35). Participants completed questionnaires at baseline and two-week follow-up on demographics, hedonic liking of study meals, perceived dietary quality, and food security. Two-way repeated measures analysis of variance was used to examine group and time effects, and group by time interactions. We also describe feasibility and satisfaction outcomes to inform future implementation. Results Sixty-six participants completed the study (94%). Participants were predominantly Hispanic or Latino(a) (63%) and African American or Black (31%) women (90%). There was a significant interaction on hedonic liking of study meals (ηp²=0.16, F(1,64) = 11.78, p < .001), such that participants that received meal kits had greater improvements in hedonic liking over time than participants in the no-prep group. We observed significant improvements in perceived dietary quality (ηp²=0.36, F(1,64) = 36.38, p < .001) and food security (ηp²=0.36, F(1,64) = 36.38, p < .001) across both groups over time, but no between group differences or significant interactions indicating one intervention was more effective than the other. Program satisfaction was high across both groups, but higher among the meal kit group (ηp²=0.09, F(1,64) = 6.28, p = .015). Conclusions Results suggest nutritious meal kits and no-prep meals may be desirable nutrition intervention strategies for pantry clients and have potential to increase food security and perceived dietary quality in the short-term. Our findings are limited by a small sample and short follow-up. Future studies should continue to test both interventions, and include longer follow-up, objective measures of dietary quality, and relevant clinical outcomes. Trial registration This trial was registered on 25/10/2022 on ClinicalTrials.gov, identifier: NCT05593510.